The Effect of Term of Payment on Customer Loyalty with Electronic Word of Mouth as Moderating Variable - Ufi Rumefi (Economics and Education Journal (Ecoducation), 2021)
This research was conducted to find out and explain the influence of Term of Payment dependent variables on independent variable Customer Loyalty with Electronic Word of Mouth as moderating variable. Samples in this study were customers of UD SUMBER AGUNG which amounted to 37 respondents, the research method used is quantitatively described with a tool SPSS.16 aids, the results of the study showed nillai t sig. the effect of Term of Payment on Customer Loyalty before moderating test of 0.000 is less than 0.05 this means that Term of Payment affects Customer Loyalty before moderating test for percentage of R-Squares effect of Term of Payment on Customer Loyalty of 57.3% the remaining 42.7% is influenced by other variables such as: complaint handling and good quality product. The test result of t. sig variable Term of Payment to Customer Loyalty after moderating with Electronic Word of Mouth as moderating variable is AbsX1_X2 (0.789>0.05) this explains that Electronic Word of Mouth as moderating variable is not able to strengthen the relationship between X to Y.